Moving eyes on pictures following visual grammar benefits meaning making: Evidence from the independent reading of Chinese preschool children. (June 2020) - Li, Linhui; Martin, Cortazzi; Baogen, Liu; Xiaomei, Gao
Children focus on pictures during storybook reading, thus, investigating children's eye movement on the pictures of storybooks may implicate how they make meaning during the process. However, very few studies have examined this issue. In this study, an experiment tracking children's eye movement with Tobii T60 was implemented for 115 children aged from 3 to 6 years, and data were analyzed based within a framework of the theory of 'Visual Grammar'. The results showed: first, children at age of three to six years clustered their eye fixations on 'participants' in pictures, which are informative regions for meaning making. Second, linguistic and visual variables all affect how soon, for how long and how many times they fixated on the participants. Third, children pay attention to participants, especially to those which have relationships representing actions: this is better for children to make meaning from pictures.